The Work of Music Theory: Selected Essays - Christensen, Thomas (Burlington Ashgate, 2014)
This collection brings together an anthology of articles by Thomas Christensen, one of the leading historians of music theory active today. Published over the span of the past 25 years, the selected articles provide a historical conspectus about a range of vital topics in the history of music theory, focusing in particular upon writings from the seventeenth and eighteenth centuries. Christensen examines a variety of theorists and their arguments within the intellectual and musical contexts of their time, in the process highlighting the diverse and idiosyncratic nature of the discipline of music theory itself.In the first section of the book Christensen offers general reflections on the meaning and interpretation of historical music theories, with especial attention paid to their value for music theorists today. The second section of the book contains a number of articles that consider the catalytic role of the thorough bass in the development of harmonic theory during the seventeenth and eighteenth centuries. In the final two sections of the anthology, focus turns to the writings of several individual music theorists, including Marin Mersenne, Seth Calvisius, Johann Mattheson, Johann Nicolaus Bach, Denis Diderot and Johann Nichelmann.The volume includes essays from hard-to-find publications as well as newly-translated material and the articles are prefaced by a new, wide-ranging autobiographical essay by the author that offers a broad re-assessment of his historical project. This book is essential reading for music theorists and seventeenth- and eighteenth-century musicologists.Contents: Introduction. Part 1 Reflections on the History of Music Theory: Music theory and its histories; Music theory in Clios mirror; Fragile texts, hidden theory. Part 2 Thorough-Bass and Music Theory: Fundamenta Partiturae: thorough bass and foundations of 18th-century composition pedagogy; The Spanish Baroque guitar and 17th-century triadic theory; The Règle de lOctave in thorough-bass theory and practice; Throughbass as music theory. Part 3 The 17th Century: Harmonia Temporis: Calvisius and musical chronology; The sound world of Father Mersenne. Part 4 The 18th century: Johann Nicolaus Bach as music theorist; Bach among the theorists; Sensus, Ratio, and Phthongos: Matthesons theory of tone perception; Nichelmann contra C.Ph.E. Bach: harmonic theory and musical politics at the court of Frederick the Great; Diderot, Rameau, and resonating strings: new evidence of an early collaboration; Bemetzrieders dream: Diderot and the pathology of tonal sensibility in the Leçons de clavecin. Index.About the Editor: Thomas Christensen is the Avalon Foundation Professor of Music and the Humanities, Associate Dean and Master of the Humanities Collegiate Division, University of Chicago, USA.
Keywords: Music theory